NAM BỘ (SOUTHERN VIETNAM) ECOLOGICAL AND CULTURE IN TALES OF BA PHI LANGUAGE - Phạm, Văn Hóa (Viện Văn học - Đại học Văn Lang, 2023)
The article shows that the tales of Ba Phi focuses on artisstic elements related to the culture, the river and water ecological environment of Nam Bộ (Southern Vietnam) region. First of all, the tales of Ba Phi can be divided into 3 main topics: The subject of forest ecological zones in Southern Vietnam, the subject of Ca Mau river-water ecological region and the subject of the working life in agricultural production in the delta ecological region. These works study the art of language elements related to the cultural and ecological environment of the river in the tales of Ba Phi into the following categories: The location names of water-ecological culture; the people and cultural life in Cà Mau’s river ecological region; the animal of the Southern Vietnam forest ecological region, and the products of the ecological region in the Nam Bộ, studying the cultural identity of the Nam Bộ ecological region through art language elements in the tales of Ba Phi, we have a better understanding of the land and the cultural life of people here